2016
DOI: 10.1111/josh.12424
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationships of Fitness, Physical Activity, and Weight Status With Academic Achievement in Adolescents

Abstract: High fitness in adolescence is associated with higher subsequent academic achievement. The promotion of PA might benefit school performance because of enhanced fitness levels in the long-term and positive influences of PA in the shortterm. The association between weight status and educational attainment remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 30 publications
8
38
1
Order By: Relevance
“…However, Manes (2015) reported that internalising symptoms assessed using a standardised inventory did not mediate the association between obesity and maths and reading achievement [ 40 ]. This finding was supported by four other studies, which assessed the mediating role of depression [ 38 , 45 , 47 , 55 ].…”
Section: Part 1: Methods and Results Of The Systematic Reviewsupporting
confidence: 79%
See 3 more Smart Citations
“…However, Manes (2015) reported that internalising symptoms assessed using a standardised inventory did not mediate the association between obesity and maths and reading achievement [ 40 ]. This finding was supported by four other studies, which assessed the mediating role of depression [ 38 , 45 , 47 , 55 ].…”
Section: Part 1: Methods and Results Of The Systematic Reviewsupporting
confidence: 79%
“…Twenty-four studies assessed the association between overweight and/or obesity and academic achievement whereas two studies related percentage body fat [ 46 , 53 ], one study BMI z scores [ 32 ] and two studies BMI [ 40 , 54 ], to children’s academic achievement. Measures of academic achievement were obtained from school records or standardised tests by 25 studies and five studies relied on teacher or self-reported academic attainment [ 37 , 42 , 44 , 52 , 55 ].…”
Section: Part 1: Methods and Results Of The Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For preadolescent children, positive effects were found for physical activity on academic performance (g � 0.26; 95% CI � 0.02 and 0.49; 3 studies) [9]. Likewise, high fitness performance in adolescence was also associated with higher subsequent academic achievement [10]. However, there are few studies that focus on the relationship between physical fitness and college students' academic performance.…”
Section: Introductionmentioning
confidence: 99%